Spectroscopy of higher bottomonia - Ferretti J. (EPJ Web of Conferences, 2015)
In this contribution, we discuss our recent unquenched quark model results for the spectrum of bb̄ mesons with self energy corrections, due to the coupling to the meson-meson continuum. Our unquenched quark model predictions for the masses of the recently discovered χb(3P) states are compared to those of a re-fit of Godfrey and Isgur’s relativized quark model to the most recent experimental data. The possible importance of continuum effects in the χb(3P) states is discussed. Finally, we show our quark model results for the radiative decays of the χb(3P) system and the open-bottom decays of bb̄ mesons.